A STUDY ON SYMBOLS USED IN SO’A PARA ZEDHE CEREMONY - Simplisius Menge Aso (JURNAL ILMIAH BAHASA DAN SASTRA, 2016)
So’a is a district where known as one of ethnics group which has many kinds of traditional ceremony. This region is located in the north side of Flores island. There are appear the variety of culture ceremony that certainly inherited from the ancestors. In each of the ceremony appears many kinds of symbol which has a certain meaning related to the human life. One of those is Para Zedhe ceremony. This traditional ceremony is held by some people who want to reach the highest social class and they will be acquainted as Mosalaki. The study was aimed to observe the meaning of symbols used in So’a Para Zedhe ceremony. The research design used descriptive qualitative method. The key instrument of this research was the researcher himself and the tools that used in this research were observation, documentation, and interview and. The analysis of the data included separating all the data that obtained from the sample and also learned the theory. Then, understanding the data and analyzing the meaning of symbols based on the theory. The result of the data analysis revealed the meaning of every symbols used in the ceremony. The symbols meaning that appeared in Para Zedhe ceremony reflected about the existence and So’a society life. Basically, these symbols were represented by the tools, animals, plants, actions, and social life. Mostly, the symbol of animals and plants were often used by people of the tribe in So’a. Moreover, the result showed that in the investigation revealed not only about the symbols, but also the values and functions in society life.